RESPON MAHASISWA PADA PENGGUNAAN WALKING GALLERY SEBAGAI METODE AJAR KEWIRAUSAHAAN BERBASIS KARAKTER MATHPRENEUR - Baharuddin (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
Walking Gallery is one of the methods used in learning by involving active student participation. Its use raises various responses from students as users of the method, so the purpose of the research is to explore more deeply related to student responses to the use of Walking Gallery as a tool to improve mathpreneur character-based entrepreneurship learning that combines elements of art, creativity, and collaboration, to develop the entrepreneurial spirit of students by prioritizing understanding of entrepreneurial concepts through a mathpreneur character-based approach (entrepreneurship based on mathematical and analytical thinking). The research method used is descriptive qualitative type. The research sample was 17 students of Mathematics Study Program, Makassar State University. The data collection used an interview guideline instrument. The research data analysis was carried out using descriptive qualitative. The results showed that students showed a positive response to the Walking Gallery method with an increase in mathpreneur character and student involvement, as well as a deeper understanding of entrepreneurship. The results of the study are expected to be able to bridge the character of students to increase creativity and business ideas that support the creation of businesses based on mathpreneur character and have uniqueness that becomes competitiveness in the community.